L’avènement du shopping mall à Rabat : les formes d’appropriation sociale d’un espace marchand et sélectif - Tarik Harroud (Ateliers d'Anthropologie)
This contribution explores social, spatial and cultural restructurings that are resulting from the arrival of shopping malls in the Moroccan capital. It aims to explore the social and spatial practices at work in these private, imported facilities.Based on investigations conducted on these sites, combining intensive observations with interviews with a sample of their users, the contribution will attempt to shed light on the modalities of their material and symbolic construction (conceived space), as well as the ways in which they are visited and socially appropriated (experienced space). The analysis of the various social and symbolic uses made of these selective places reveals how these spaces are subject to heterogeneous visits and are the scene of new forms of sociability at the scale of Rabat.